2012
DOI: 10.4028/www.scientific.net/amr.452-453.1014
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Oxygen Transfer Efficiencies in the Different Methods Used in the Technique of Hypolimnetic Aeration

Abstract: Thermal stratification of lakes and reservoirs can result in substantial hypolimnetic oxygen depletion, which may have a negative impact on the cold-water fisheries, the drinking water treatment process, and water quality downstream of hydropower reservoirs. Several techniques of aeration are presented in this study, to describe their effectiveness in control of physical and chemical parameters, that compromising the balance ecological and the thermal stratification in water supplies. As a result, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Compared with the aerators commonly used for microporous aeration, the linear microporous aeration system has been well applied by the Tennessee Valley Authority. The bubbles generated by this system have the characteristics of plume diffusion, and the efficiency of oxygen mass transfer in deep water is more than 90%. , However, when linear microporous aeration is applied to repair black and odorous water in rivers and lakes with a small water depth, the oxygen mass transfer efficiency is inhibited. The utilization rate of oxygen decreases with the decrease in water depth; when the water depth is 2–5 m, the utilization rate of oxygen is generally about 15%, which results in a large waste of aeration energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the aerators commonly used for microporous aeration, the linear microporous aeration system has been well applied by the Tennessee Valley Authority. The bubbles generated by this system have the characteristics of plume diffusion, and the efficiency of oxygen mass transfer in deep water is more than 90%. , However, when linear microporous aeration is applied to repair black and odorous water in rivers and lakes with a small water depth, the oxygen mass transfer efficiency is inhibited. The utilization rate of oxygen decreases with the decrease in water depth; when the water depth is 2–5 m, the utilization rate of oxygen is generally about 15%, which results in a large waste of aeration energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its advantages of simple operation and low cost, it has been widely used. Microporous aeration has the advantage of high oxygen utilization rate because of the smaller bubble size, which leads to its longer residence time and larger gas–liquid contact area with water, and it has been applied in the rehabilitation of various municipal and industrial wastewaters and has achieved good results. , Previous investigations showed that the water restoration effect is closely related to the oxygen mass transfer process. , The linear microporous hose aeration applied in Tennessee Valley has an oxygen utilization rate of over 90% in deep water; , however, the oxygen utilization rate is only about 15% with a relatively shallow water depth (2–5 m), which limits the application of the microporous aeration technology. Therefore, how to improve the oxygen mass transfer efficiency of microporous aeration is an urgent problem to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are concerned at the first hand on the design of lab‐scale aeration equipment, the transfer of air to the water and the effects on the aeration of the water body. There are also review articles comparing different studies (Beutel and Horne, 1999; Mostefa et al ., 2012; Singleton and Little, 2006). Lab‐scale studies are followed by pilot‐scale implementations in the field and mathematical modelling approaches (Taggart and Mcqueen, 1982; Ashley et al ., 1987, 1991; Little, 1995; Burris et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%